Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Keterampilan Oral Communication Peserta Didik Kelas X MIPA 4 SMA Negeri 5 Surakarta - Indah Purbo Wahyuni; Alanindra Saputra; Harlita Harlita (Universitas Sebelas Maret, 2019)
The aim of this research was to determine the improvement of oral communication skills through the PjBL learning model of class X MIPA 4 Surakarta Public High School 5. The research subjects used were students of class X MIPA 4 consisting of 32 students. Research is classroom action research (CAR) based on problems that occur in the class. Data and sources of research data about oral communication skills obtained through observation sheets, closed interviews with teachers and students, and documentation using the PjBL learning model. Data collection by conducting observations, interviews, and documentation.Validation of data using triangulation techniques include observation, interviews, and documentation. Data analysis techniques are done by data reduction, data presentation, and conclusion drawing. The results of the research conducted concluded that the application of the PjBL learning model in learning activities of Kingdom Animalia material using projects showed that there was an increase in oral communication components of students by 40% so that oral communication skills of students increased to 60% -72.31%.